(2S, 3S)‐2, 6‐Dimethylheptane‐1, 3‐diol, the oxygenated side chain of 22(S)‐hydroxycholestrol, and its synthetic precursor (R)‐4‐benzyl‐3‐[(2R, 3S)‐3‐hydroxy‐2, 6‐dimethylheptanoyl]‐1, 3‐oxazolidin‐2‐one. (16th May 2013) - Høgmoen Åstrand, Ove Alexander; Iqbal, Zeshan; Sandberg, Marcel; Kase, Eili T.; Görbitz, Carl Henrik; Rongved, Pål
<x xml:space="preserve">Abstract</x> (2S, 3S)‐2, 6‐Dimethylheptane‐1, 3‐diol, C9H20O2, (I), was synthesized from the ketone (R)‐4‐benzyl‐3‐[(2R, 3S)‐3‐hydroxy‐2, 6‐dimethylheptanoyl]‐1, 3‐oxazolidin‐2‐one, C19H27NO4, (II), containing C atoms of known chirality. In both structures, strong hydrogen bonds between the hydroxy groups form tape motifs. The contribution from weaker C—H...O hydrogen bonds is much more evident in the structure of (II), which furthermore contains an example of a direct short Osp3...Csp2 contact that represents a usually unrecognized type of intermolecular interaction.